Affiliate Marketing Strategies for Effective Product Promotion in the Digital Era: Literature Review - Lidya Veronica Christy Rihidima; Mima Kurniasih; Billy Purwocaroko Noeringtyas; Selvi Permata Groda; Muazila Norisnita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how affiliate marketing contributes to the effectiveness of product promotion in the digital era. Using a Systematic Literature Review (SLR) approach, this research synthesizes findings from 15 relevant peer-reviewed articles published in recent years. The analysis highlights four key strategies that influence the success of affiliate marketing: information quality, subjective knowledge, interactivity, and affiliate characteristics. Results show that high-quality information builds consumer trust, while subjective knowledge helps affiliates deliver persuasive messages. Interactivity, especially through live streaming and two-way communication, enhances audience engagement. Furthermore, emotional expression, credibility, and authenticity of affiliates significantly influence consumers' purchasing decisions. The study concludes that affiliate marketing is a cost-effective promotional strategy that enhances product visibility and purchase intention through trusted intermediaries. These findings provide important implications for businesses to develop more strategic, data-driven affiliate marketing campaigns.